ANALISIS PENINGKATAN KUALITAS DENGAN PERANCANGAN KRITERIA KUALITAS PRODUK BAJU DI PT BBA BATAM - Dollun, Mario Bala; Fajrah, Nofriani (LPPM Universitas Putera Batam, 2021)
A common tool or method for developing directly customer-driven products is Quality Function Deployment (QFD). From a customer's point of view, product quality is an important thing to have and it exists in products, especially clothing, because it has a long shelf life. For this, the main objective of this research is to understand what attributes of polo products customers want through Voice of Customer (VOC) questionnaire, so that the company can improve the quality of polo products. After obtaining the Voice of Customer (VOC) data, continue to use House of Quality (HOQ) for data processing. According to the calculations made by the House of Quality (HOQ), it can be seen that the quality standards with the highest priority value are non-bleaching colors, durable materials, comfortable leather materials, soft texture, unbreakable threads and clean pins. Value is 5 importance to the customer The highest technical importance rating value is 432.1, the absolute importance value is 229, and the relative importance value of using high-quality fabrics is 12.19%.